Efficient Metal‐Free Synthesis of Various Pyrido[2′, 1′:2, 3]imidazo‐ [4, 5‐b]quinolines. Issue 37 (16th August 2013) - Arnould, Mathieu; Hiebel, Marie‐Aude; Massip, Stéphane; Léger, Jean Michel; Jarry, Christian; Berteina‐Raboin, Sabine; Guillaumet, Gérald
<x xml:space="preserve">Abstract</x> Dancing with diversity: The synthesis of diverse pyrido[2′, 1′:2, 3]imidazo[4, 5‐b]quinolines bearing several substitution patterns was developed based on combining a multicomponent reaction (Groebke–Blackburn–Bienaymé reaction) with an original cyclization as a secondary transformation (see scheme; DBU=1, 8‐diazabicyclo[5.4.0]undec‐7‐ene).<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>